(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article provides a comprehensive examination of accents, exploring their importance in communication, cultural identity, and social interactions. Accents are shown to be more than mere linguistic features; they are symbolic of cultural heritage and social belonging, helping individuals to identify with specific communities. The article outlines several key functions of accents, including their roles in differentiating social groups, aiding language development, and expressing emotion. Additionally, the article addresses the impacts of accent bias, a form of prejudice that can lead to stereotypes and affect professional opportunities. The piece advocates for increased awareness of linguistic diversity and encourages overcoming accent bias, promoting inclusivity in multicultural settings. It emphasizes the need for greater representation of diverse accents in media and society to foster understanding and empathy. Through this exploration, the article highlights the multifaceted role of accents, underscoring their significance in shaping individual identity and enhancing global cultural exchange.